Outcomes of metastatic gestational trophoblastic neoplasia: Fourteen year experience from a northern Thailand tertiary care center - Suprasert P. (2017)
Metastatic gestational trophoblastic neoplasia (GTN) is an uncommon cancer. The principal treatment consists of chemotherapy with or without surgery or radiotherapy. We here retrospectively reviewed the outcomes of metastatic GTN treated at our institute between January, 1999 and December, 2013. Sixty-three patients met the criteria. The median age was 30.0 years and almost 90% were referral cases. Nearly 40% of the studied patients presented with vaginal bleeding while 22.2% were asymptomatic. The most common antecedent pregnancy was hydatidiform mole (57.1%) followed by term pregnancy (20.6%). The median interval time from antecedent pregnancy to the development of GTN was three months and the median pretreatment B-hCG was 58,274 mIU/ml. Stage III (74.6%) was the most common staging followed by stage IV (20.6%) and stage II (4.8%). The most frequent surgery was hysterectomy (31.7%). Thoracotomy and craniotomy were performed in three and two patients, respectively. The most common first line chemotherapy regimen was methotrexate and folinic acid (36.5%) followed by EMA (etoposide, methotrexate, actinomycin D) (34.9%), EMACO (etoposide, methotrexate, actinomycin D, cyclophosphamide, vincristine) (17.5%) with the remission rate of 66.7%. Nearly one-third of the patients were given a subsequent chemotherapy regimen after failure with the first line therapy and showed a final response rate of 73.0%. However, in stage IV, the response to first line treatment was only 38.5%. In conclusion, the outcomes of metastatic GTN were poor especially with the higher stages.